Risk management practice during crisis and its relationship with performance: the moderating role of governance / Umniati Raianu Azmil Umor and Tuan Zainun Tuan Mat - Azmil Umor, Umniati Raianu; Tuan Mat, Tuan Zainun (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2025)
Every organization is bound to encounter different issues during a crisis. Risks that arise during the crisis need to be managed effectively to support the business decisions made by the management. Hence, effective management through the corporate governance role is essential to ensure that the company can sustain its performance during a crisis. This study examined the level of risk management practiced by companies during a crisis, its relationship with performance, and the moderating role of governance between risk management practices and performance. This study utilised secondary data from 60 annual Public Listed Companies (PLCs) reports for two consecutive years, 2020 and 2021. The sample consisted of the PLCs from three business sectors, i.e., manufacturing, retail, and service. The data were analysed and regressed using the SPSS software package. The results revealed an insignificant influence on risk management and performance. However, the moderating roles of governance in risk management practices and performance were significant. It indicates that effective risk management practice alone is insufficient to sustain the performance of the governance role and is ineffective in using the risk management information in making business decisions. Effective risk management leads to better decisions on the board and company growth.